2010
DOI: 10.1590/s1806-37132010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Fatores motivacionais que contribuem para a busca de tratamento ambulatorial para a cessação do tabagismo em um hospital geral universitário

Abstract: Objective: To describe the reasons smokers give for seeking smoking cessation treatment, correlating those reasons with sociodemographic characteristics, clinical data, stage of readiness to change, and severity of nicotine dependence. Methods: Between February of 2008 and February of 2009, we evaluated 53 smokers who were naive to smoking cessation treatment and sought such treatment at the psychoactive substance abuse outpatient clinic of a university general hospital. The instruments used in the study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
2
10
0
15
Order By: Relevance
“…The sociodemographic and economic characteristics of the sample were similar to those described in other similar studies (4,5,7,(11)(12)(13)(14)(15) . Patients were, on average, 54 years old, and had therefore reached an age at which the comorbidities associated with lifestyle factors often begin to appear.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The sociodemographic and economic characteristics of the sample were similar to those described in other similar studies (4,5,7,(11)(12)(13)(14)(15) . Patients were, on average, 54 years old, and had therefore reached an age at which the comorbidities associated with lifestyle factors often begin to appear.…”
Section: Discussionsupporting
confidence: 76%
“…The association between the diffi culty of quitting and proximity to other smokers has been evidenced by several studies (5,13,17) . This fi nding reinforces the need to involve family and friends in cessation interventions as a way to encourage the smoker to remain abstinent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This trend of prevalence of patients with high levels of tobacco consumption and dependence in reference services that treat tobacco-addicted individuals had already been reported by two other previous studies. A survey conducted with 53 smokers who, between 2008 and 2009, sought a treatment center due to addiction to tobacco and other drugs in the city of Campinas (SP) 40 , showed a similar population profile, with a prevalence of severe nicotine dependence (FTND > 6) in 76.5% of women and 52.6% of men who sought help to stop smoking, and this was decision strongly influenced by the stimulus provided by the family. In another reference center for treatment of smoking in Londrina (PR), Castro et al 10 also demonstrated mean FTND scores > six and tobacco load > 20 pack-years, in approximately 60% of the assessed smokers.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…14,15 : consiste de uma lista com 21 itens que são afirmações descritivas de sintomas de ansiedade e mede a intensidade deles (alfa de Cronbach = 0,92). A pontuação dos sintomas varia entre 0 e 63, e os resultados podem ser: mínimo (0-10), leve (11)(12)(13)(14)(15)(16)(17)(18)(19), moderado (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) e grave (31-63). Para fins de análise, a amostra foi dicotomizada, estabelecendo que a pontuação de 0 a 19 fosse caracterizada como mínima e/ou leve e a acima de 20 foi considerada como moderada a grave, assim como estudo prévio 16 .…”
Section: Introductionunclassified